Mediterranean winter rainfall in phase with African monsoons during the past 1.36 million years - Wagner, Bernd; Koutsodendris, Andreas (Nature, 2019)
Comparisons between past regional drivers of precipitation extremes found time series data from Lake Ohrid and modern climate models of the Mediterranean may help to reduce simulation uncertainties in predictions of the Mediterranean climate.